Το υδρογόνο ως πρόσθετο καυσίμου σε μηχανές εσωτερικής καύσης - Αγαθοκλέους, Μαργαρίτα (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος ,Τεχνολογικό Πανεπιστημίο Κύπρου, 2012)
Since the beginning of 1950 the energy problem, has slowly made its appearance first, as a philosophical thought. Although the fact that in 1950 the estimated exploited reserves of fossil fuels had sufficiency for 20 years, there was some sobriety in relation to energy demand. The energy crisis of 1973 led to the deterioration of energy problems. Due to the energy problem which is even more intense today and the reserves of the fossil fuels that are expected to be exhausted within the next 60 years, people should turn their attention to other energy sources or carries. One promising strategy to solve the energy problem is the exploitation of hydrogen (H2) which is abundant in nature but bound to other molecules. This «clean energy» - hydrogen economy, targets the replacement of the conventional mineral fuels, as soon as possible. The benefits of the use of the H2 as an energy source are multiple. Among them is the energy sufficiency, the economical independence from hydrocarbon economy, the economic decentralization and the protection of the environment. The purpose of this Thesis is to use hydrogen as a fuel additive in Internal Combustion Engines (ICE) to improve combustion, reduce consumption of fossil fuels and simultaneously reduce emissions of sulfur dioxide (SO2), carbon monoxide (CO), carbon dioxide (CO2), particulate matter (PM) and unburned hydrocarbons (HCs). The latter gases pollutants are considered to be the major greenhouse gases that cause the climate change witnessed nowadays. Hydrogen is generated through the electrolysis of water and is not stored but produced on demand. Hydrogen is used in the engine as a fuel additive so the engines do not have to be built from scratch, but it can be fed into existing engines. The first chapter presents an overview of the characteristics focusing on its presented of hydrogen the physical and chemical properties. A reference is made to the energy problem and hydrogen is as an energy source and carries that can alleviate this problem and the areas that research on hydrogen evolves. Moreover, a brief presentation of the methods used to produce the H2 is mentioned, such as water electrolysis. An important aspect is then studied concerning the safety measures that need to be considered prior the use of H2. Finally, the advantages and disadvantages of hydrogen compared with other conventional fuels are presented. The second chapter includes comprehensive references of the use of hydrogen as a fuel. The process of water electrolysis for hydrogen production is therefore described. The ABSTRACT ix amount of energy produced from the combustion of hydrogen is then compared of the resulting from the combustion of oil as fuel. The gaseous products of H2 combustion are mentioned at the end of this chapter. Thus, an overview of the regulations for the prevention of air pollution from ships (International Convention MARPOL 73/78) is been made. The third chapter includes a description of the experimental procedure followed in this thesis. In this chapter the experimental apparatus used for internal combustion engines is presented. The instruments used and the methodology followed for the measurement of the concentration gaseous emissions, temperature and fuel consumption are mentioned. Finally, the materials used for the construction of the electrolysis apparatus are described. In order to performing the experiments on the burner and the electrical generator and ultimately on ships, the water electrolysis was first contacted in order to produced hydrogen and oxygen. The device constructed consists of eight fuel cells. All of them were used in the burner while only six of them for the electrical generator. Also throughout the experimental procedure, a power converter was used to supply the necessary power to the entire electrolysis process. The exhaust gases produced from the internal combustion engine were measured with the use of a portable gas analyzer, as well as the temperature of the ICE and of the exhaust gases. The fourth chapter presents and analyzes the results obtained from the experiments conducted in internal combustion engines. The results obtained concerned the use of conventional fuel and hydrogen fuel mixture. Measurements conducted concern the temperature of the engine and the conventional fuel consumption and the concentration of gaseous emissions. The results obtained from the aforementioned measurements are summarized as followed: the concentration of SO2 when H2 is added to the burner for combustion decreased by 22%, while in the electrical generator exhaust stream was decreased by 52%. The concentration of CO also decreased when H2 was added, to 38,5% and 34% in the boiler and electrical generator respectively. On the contrary, the concentration of NOX was found to be 5% and 2% increased for the burner and the electrical generator respectively when H2 was added as a fuel. The concentration of particulate matter and unburned hydrocarbons could not be measured, however they are expected to be reduced, based on certain observations concerning the color of smoke (opacity) and the analyzer’s filters. It was found that the use of the mixture of H2/O2 increased the temperature of the ICE and the exhaust gases to 10-15°C. Calculations were ABSTRACT x performed in order to estimate the fuel consumption with the use of H2/O2 as a fuel additive. It was found that 9.504 L/month of conventional fuel were conserved for the burner (13.115 €/month), while the electrical generator conventional fuel consumption was reduced by 2.016 L/month (2.782 €/month). Finally, the fifth chapter remarks the general conclusions resulting from this thesis as well as a summary of techniques that can combine the process of water electrolysis with hydrogen combustion in internal combustion engines in order to achieve optimization. The conclusion that can be easily derived is that H2 is the fuel of the future since it is abundant and does not burden the atmosphere with harmful pollutants that cause many environmental problems. As seen from the results obtained, H2 can effectively replace the conventional fuels used for energy production.
Keywords: Ηydrogen; Fuel; Υδρογόνο; Κάυσιμο